Chemical Composition of Spirulina platensis which Cultivated in Photobioreactors with Different Photoperiodes - Sari Afriani; Uju Uju; Iriani Setyaningsih (Jurnal Pengolahan Hasil Perikanan Indonesia, 2018)
Spirulina platensis known as filamentous cyanobacteria, single-celled and spiral-shaped. It is often  called  blue-green microalgae. This study aimed to determine the effect of photoperiod on the characteristic of S. platensis which were cultivated in a controlled photobioreactor (FK) and uncontrolled photobioreactor (FTK). The observed characteristics include the growth curves, dried weight of biomass, carbohydrates content,  protein, fat and bioactive compounds. The research used Completely Randomized Design (CRD) with two replications. S. platensis was cultured in 10 L volume using combination of urea, organic fertilizer RI1 and Plant catalyst (URC medium) at 24:0, 16:8, 12:12 and 6:18 (light hours:dark hours) photoperiods. The results showed the controlled photobioreactor (FK) with 24:0 photoperiods had Optical Density (0.882), dried biomass (0.31 g/L) and carbohydrate (25.85%) highest than those of other treatments. Uncontrolled photobioreactor (FTK) with photoperiods 12:12 and 16:8 had the higher protein content (58,44%) than of other treatments. The highest total fat (6.60%) occurred in photoperiod 6:18. The results of bioactive compounds based on phytochemical analysis for the whole treatment positively contained flavonoids, phenols, steroids and saponins.